2021
DOI: 10.1038/s41467-020-20169-1
|View full text |Cite
|
Sign up to set email alerts
|

Pillar-beam structures prevent layered cathode materials from destructive phase transitions

Abstract: Energy storage with high energy density and low cost has been the subject of a decades-long pursuit. Sodium-ion batteries are well expected because they utilize abundant resources. However, the lack of competent cathodes with both large capacities and long cycle lives prevents the commercialization of sodium-ion batteries. Conventional cathodes with hexagonal-P2-type structures suffer from structural degradations when the sodium content falls below 33%, or when the integral anions participate in gas evolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(73 citation statements)
references
References 60 publications
3
70
0
Order By: Relevance
“…Second, staged business reopenings and the emergence of new virus variants have sometimes led to accelerating or runaway epidemics. These may be due to sudden changes in social behavior, but we showed that accelerating epidemics can also result from decreases in contact tracing efficiency [26]. Increasing contact tracing capacity could limit this epidemic acceleration as cases increase, which suggests that training a reserve capacity of tracers and being able to deploy a mobile tracing force could help limit runaway epidemics.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Second, staged business reopenings and the emergence of new virus variants have sometimes led to accelerating or runaway epidemics. These may be due to sudden changes in social behavior, but we showed that accelerating epidemics can also result from decreases in contact tracing efficiency [26]. Increasing contact tracing capacity could limit this epidemic acceleration as cases increase, which suggests that training a reserve capacity of tracers and being able to deploy a mobile tracing force could help limit runaway epidemics.…”
Section: Discussionmentioning
confidence: 79%
“…Numerous studies have examined the effectiveness and limitations of TTIS on transmission of SARS-CoV-2 and other pathogens [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Many studies have shown that TTIS can substantially reduce the pathogen reproductive number, R t , but its efficacy depends on the importance of pre-symptomatic and asymptomatic transmission, delays between symptom onset and being tested, and the fraction of infections that are tested and traced [14,19,22,24].…”
Section: Introductionmentioning
confidence: 99%
“…Phase transitions are very common in layered cathode materials, most especially during Li deintercalation [35,36]. When delithiation takes place, metal redox potentials overlap with oxygen 2p energies leading to oxygen anion oxidation and molecular oxygen release.…”
Section: Hindering Phase Transitions Through Metal Oxide Coatingmentioning
confidence: 99%
“…Irreversible surface/bulk phase transition upon cycling has been reported as one of the prevalent origins for the performance degradation of layered cathodes 8 , 9 . Several prominent studies showed that surface reconstruction, such as layered to spinel/rock-salt, can initiate from the cathode surface, and then gradually propagate into the bulk structure during a high-voltage charge.…”
Section: Introductionmentioning
confidence: 99%